Scalable, Green Chain Transfer Agent for Cationic RAFT Polymerizations. Issue 4 (23rd December 2022) - Spring, Scott W.; Cerione, Chloe S.; Hsu, Jesse H.; Shankel, Shelby L.; Fors, Brett P.
Comprehensive Summary: Cationic polymerizations of vinyl ethers have gained recent attention due to their ability to produce robust, biorenewable materials. These developments have been largely enabled by the advent of cationic reversible addition−fragmentation chain‐transfer (RAFT) polymerization; however, the scalability and sustainability of this method are hindered by current chain‐transfer agents (CTAs), which exist as viscous, colored oils requiring complex syntheses and solvent‐intensive purification. Herein, we produce a solid, colorless CTA through a green synthetic route in 83% yield on a 50‐gram scale. We investigate the utility of this CTA in chemical, electrochemical, photochemical, and acid‐initiated methods, revealing that it achieves efficient polymerization with excellent control over molecular weight, low dispersity values, high chain end fidelity, and temporal control in cationic RAFT polymerizations. Abstract : We produce a solid, colorless CTA through a green synthetic route in 83% yield on a 50‐gram scale. Investigation of this CTA in chemical, electrochemical, photochemical, and acid‐initiated cationic RAFT methods revealed that it achieves efficient polymerization with excellent control over molecular weight, low dispersity values, high chain end fidelity, and temporal control.